Researching Effective Strategies to Improve Insulin Sensitivity in Children and Teenagers - RESIST. A randomised control trial investigating the effects of two different diets on insulin sensitivity in young people with insulin resistance and/or pre-diabetes. - De Sukanya; Parker Robert; Broderick Carolyn R; Chisholm Kerryn; Burrell Susie; Woodhead Helen J; Steinbeck Katharine; Noakes Manny; Baur Louise A; Garnett Sarah P; Shrinivasan Shubha; Hopley Lori; et al. (BMC, 2010)
Abstract Background Concomitant with the rise in childhood obesity there has been a significant increase in the number of adolescents with clinical features of insulin resistance and prediabetes. Clinical insulin resistance and prediabetes are likely to progress to type 2 diabetes and early atherosclerosis if not targeted for early intervention. There are no efficacy trials of lifestyle intervention in this group to inform clinical practice. The primary aim of this randomised control trial (RCT) is to determine the efficacy and effectiveness of two different structured lifestyle interventions differing in diet composition on insulin sensitivity, in adolescents with clinical insulin resistance and/or prediabetes treated with metformin. Methods/design This study protocol describes the design of an ongoing RCT. We are recruiting 108 (54 each treatment arm) 10 to 17 year olds with clinical features of insulin resistance and/or prediabetes, through physician referral, into a multi-centred RCT. All participants are prescribed metformin and participate in a diet and exercise program. The lifestyle program is the same for all participants except for diet composition. The diets are a high carbohydrate, low fat diet and a moderate carbohydrate, increased protein diet. The program commences with an intensive 3 month dietary intervention, implemented by trained dietitians, followed by a 3 month intensive gym and home based exercise program, supervised by certified physical trainers. To measure the longer term effectiveness, after the intensive intervention trial participants are managed by either their usual physician or study physician and followed up by the study dietitians for an additional 6 months. The primary outcome measure, change in insulin sensitivity, is measured at 3, 6 and 12 months. Discussion Clinical insulin resistance and prediabetes in the paediatric population are rapidly emerging clinical problems with serious health outcomes. With appropriate management these conditions are potentially reversible or at least their progression can be delayed. This research study is the first trial designed to provide much needed data on the effective dietary management for this cohort. This study will inform clinical practice guidelines for adolescents with clinical insulin resistance and may assist in preventing metabolic complications, type 2 diabetes and early cardiovascular disease. Trial registration Australian and New Zealand Clinical Trials Registration Number ACTRN12608000416392